2013
DOI: 10.1227/01.neu.0000429852.45073.73
|View full text |Cite
|
Sign up to set email alerts
|

Successful Deep Brain Stimulation Surgery With Intraoperative Magnetic Resonance Imaging on a Difficult Neuroacanthocytosis Case

Abstract: DBS surgery of the bilateral globus pallidus pars interna may be useful in controlling the hyperkinetic movements in neuroacanthocytosis. Because of the high propensity for seizures in this disorder, DBS performed under general anesthesia, with intraoperative magnetic resonance imaging guidance, may allow successful implantation while maintaining accurate target localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…These findings, although observed in few patients, suggest that epilepsy may not be a contraindication or a serious concern for GPi-DBS in ChAc, but further studies are needed to address this point. Indeed, a recent case reported possible intraoperative seizures and also post-operative intracranial hematoma in a 32-years-old patient with non-molecularly proven ChAc [40]. Two years later, the patient underwent a second DBS operation leading to a marked improvement of his dystonia, chorea and overall quality of life 2 and 8 months postoperatively [40].…”
Section: Discussionmentioning
confidence: 99%
“…These findings, although observed in few patients, suggest that epilepsy may not be a contraindication or a serious concern for GPi-DBS in ChAc, but further studies are needed to address this point. Indeed, a recent case reported possible intraoperative seizures and also post-operative intracranial hematoma in a 32-years-old patient with non-molecularly proven ChAc [40]. Two years later, the patient underwent a second DBS operation leading to a marked improvement of his dystonia, chorea and overall quality of life 2 and 8 months postoperatively [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of these overall positive findings, some limitations must be highlighted in the published case reports. First, the data come from case reports or case series studies and articles involving operations performed by different surgeons and evaluations performed by different doctors (Table 1 4,[10][11][12][13][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] ), which may affect surgical efficacy evaluation. The majority of the reported cases did not use blind methods to evaluate symptoms, which could bias results.…”
Section: Discussionmentioning
confidence: 99%
“…As the clinical response to GPi‐DBS are symptom‐specific, discussions may be best placed in this context. For cardinal features of ChAc, it seems that chorea and orolingual dyskinesia have had rapid and satisfactory responses to both HFS and LFS . Interestingly, Guehl reported that chorea was improved only under LFS and exacerbated with HFS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Guehl reported that chorea was improved only under LFS and exacerbated with HFS. For dystonia, varied improvements have been found with HFS and LFS, which appears to be delayed , less satisfactory and less frequency‐sensitive than chorea. Our findings on the symptoms of dysarthria are in accordance with previous reports that have noted dysarthria is generally insensitive to GPi‐DBS or even exacerbated after DBS regardless of stimulation frequency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation